Tanggapan Masyarakat terhadap Pelaku Minuman Keras di Kelurahan Hedam Distrik Heram Kota Jayapura - Wanma, Melki Benjamin; Lefaan, Avelinus (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2023)
Social problems will continue to emerge unavoidably and at the same time will continue to affect the dimensions of everyone's life. Liquor is a type of drink that contains addictive substances (alcohol). This is what then makes every drink user sometimes commit criminal/deviant acts which are of course detrimental and troubling to society, such as bullying, fights, and domestic violence. the dangers of this liquor can not only be felt by certain persons but the behavior of the liquor harms many parties. This study aims to determine how the community responds to alcoholics in Hedam Village, Heram District, Jayapura City. The research method used is qualitative with a phenomenological approach, the number of samples is 10, and the purposive sampling technique data collection methods observation, interviews, and documentation. qualitative data analysis namely data reduction, data presentation, and withdrawal. The results that are known from this research are the public's response to the perpetrators of drinking, what are the effects of drinking. The conclusion is that alcohol can influence alcoholics so it has a harmful impact on oneself and others. Recommendations from the government and related institutions can take this behavior problem due to alcohol seriously because alcohol is one of the highest causes of crime and death in the Land of Papua.